Anthropolinguistic Tools to Study Political Linguistics.The Case of Donald Trump’s 2020 Campaign Discourse - Strukowska, Marta E.; Chruszczewski, Piotr P. (2022)
The paper presents an anthropolinguistic study of Donald Trump’s 2020 presidential campaign discourse. The studycan be situated within the scope of political linguistics. The interdisciplinary method of research applied here restsupon the understanding of human communication functioning in terms of communicational grammars of specifidiscourses that comprise rules of language use set against the background of immediate contexts of use. The key ideaunderbracing this study is that language is a rule-governed, conventions-based system of practice (e.g., de Saussure[1916] 2011, Sapir 1921, Hymes 1972, Saville–Troike [1982] 2003, Lucy [1996] 1999) and a conventional typeof performance which allows for building a nexus of typified relations. Another overarching goal of this paper isto show that human interaction is mostly both a structurally hardwired and functionally (pragmatically) drivenlinguistic practice. The analysis sets out to explore Donald Trump’s texts according to the AnthropolinguisticModel of Communication (AMC) (Strukowska 2022) as a pattern recognition model that provides a contextualoverview of elements of communication and functions as a solid platform for documenting discursive practices(Chruszczewski 2011: 199–263).
Keywords: Trump, Donald